Research Progress on the Natural Product Aloperine and Its Derivatives - Cheng, Yu; Rauf, Abdur; Pan, Xiandao (Mini Reviews in Medicinal Chemistry, 2022)
In this review, an effort towards presenting an all-around account of the recent progress on the natural product, aloperine, is made, and the antivirus structure-activity relationship of its derivatives is also summarized comprehensively. In addition, the principal pharmacological effects and corresponding molecular mechanisms of aloperine are discussed. Some new structural modifications of aloperine are also given, which might provide brief guidance for further investigations on the natural product aloperine.
Keywords: molecular mechanisms